Construction and Structural Analysis of a Scale to Measure Research Culture in Peruvian University Students - Meregildo-Gómez, Ruth; Mas-Sandoval, Romy Kelly; Cruz-Aguilar, Reemberto; Yglesias Alva, Lucy Angélica (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The University as a center of research and knowledge must promote a research culture. The article aims to present the construction and structural analysis of a scale to evaluate the research culture in university students, made up of six dimensions and thirty items rated on the Likert scale with five response options. The scale was applied to 438 students in their last year of studies from sixteen Schools of a University in northern Peru, after its validation by five experts. The exploratory and confirmatory factorial analysis allowed validating the multidimensional structure and its reliability was established with the omega coefficient (w=0.96).